2015
DOI: 10.1371/journal.pone.0144487
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Tuberculosis Reinfection Soon after Cure of a First Disease Episode Is Extremely High in a Hyperendemic Community

Abstract: Elevated rates of reinfection tuberculosis in various hyperendemic regions have been reported and, in particular, it has been shown that in a high-incidence setting near Cape Town, South Africa, the rate of reinfection tuberculosis (TB) disease after cure of a previous TB disease episode is about four times greater than the rate of first-time TB disease. It is not known whether this elevated rate is caused by a high reinfection rate due, for instance, to living circumstances, or a high rate of progress to dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…After following a cohort of largely HIV-coinfected ambulatory individuals successfully treated for pulmonary tuberculosis disease in a high burden setting for a median of 6 years, we found that 11% (95% CI 7.2 to 13.8%) had bacteriologically proven recurrent tuberculosis and an additional 3% (95% CI 1.2 to 4.8%) had empirically-diagnosed recurrent tuberculosis. This is consistent with other studies performed in high burden settings [ 2 , 27 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…After following a cohort of largely HIV-coinfected ambulatory individuals successfully treated for pulmonary tuberculosis disease in a high burden setting for a median of 6 years, we found that 11% (95% CI 7.2 to 13.8%) had bacteriologically proven recurrent tuberculosis and an additional 3% (95% CI 1.2 to 4.8%) had empirically-diagnosed recurrent tuberculosis. This is consistent with other studies performed in high burden settings [ 2 , 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…Patients who have recently completed treatment for tuberculosis (TB) are at elevated risk of recurrent TB disease, either as a result of relapse or reinfection [ 1 , 2 ]. When individuals are diagnosed with recurrent TB, they are less likely to complete treatment and suffer higher mortality than those with first episodes of TB [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant proportion of TB patients successfully cured after chemotherapy exhibit recurrent disease. Similar to recrudescence of a latent infection, many of these cases can be ascribed to reactivation of residual bacilli after treatment failure but, especially in high-incidence areas, exogenous re-infections seem to account for a significant proportion of TB recurrence ( De Boer and Van Soolingen, 2000 , Guerra-Assuncao et al, 2015 , Sonnenberg et al, 2001 , Uys et al, 2015 , Verver et al, 2005 ). Such TB patients could simply just be inherently more susceptible, thus exhibiting recurrent infections.…”
Section: Discussionmentioning
confidence: 99%
“…The drainage of the infection on exposed individuals is given by 75,76 , which is assumed to be reduced by the possibility of endogenous or exogenous reactivation of the infection, defined as and , respectively. Thus, bacillary drainage is defined as: = 0.1 -a -r. Uys et al 77 determined that recovered subjects have a sevenfold higher chance of developing disease, which is given by w in our model. The birth rate ( ) is determined from the mean number of births per fertile woman/year ( ).…”
Section: 1-tbspectr Modelmentioning
confidence: 91%